STRATEGI MENINGKATKAN JIWA WIRAUSAHA BAGI MAHASISWA DI PERGURUAN TINGGI - Nurhasanah, Nurhasanah; Mayefis, Reska (Ensiklopedia of Journal, 2025)
Abstract: Students' interest in entrepreneurship still faces various challenges, such as lack of understanding, limited access to capital, and fear of the risk of failure. This requires the role of universities in producing graduates who have an entrepreneurial spirit. The purpose of writing this article is to analyze strategies for increasing the entrepreneurial spirit of students in higher education using the literature study method. The research results show that strategies to increase the entrepreneurial spirit among university students can be carried out through various integrated approaches. This strategy includes formal education, entrepreneurship training, practice-based programs, and collaboration with the industrial sector, which are strategic steps that can be implemented to foster students' entrepreneurial spirit. These things complement each other to build students' entrepreneurial spirit. Formal education provides a theoretical foundation, while practice-based training and programs strengthen students' skills and experience. Involvement in the business world ensures that students understand the realities of business and the challenges they will face. However, there are challenges that need to be overcome, such as a lack of access to capital and the lingering fear of failure. Therefore, universities need to develop a more inclusive entrepreneurial ecosystem and provide supporting facilities, such as business incubators and funding programs. Through a structured strategy, it is hoped that students will not only have the interest but also the courage to start and develop a business. This is in line with the university's goal of producing a young generation who is creative, innovative and globally competitive.Keywords: Strategy, Improving, Entrepreneurial Spirit